1992
DOI: 10.1002/aja.1001930405
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of two antigens associated with mouse intestinal crypts

Abstract: Two monoclonal antibodies were prepared against the duodenal mucosa of fourday‐old mice (MIM‐1/39 and MIM 1/130). The expression of the antigens was associated with the crypts of the small and large intestine in the fetus and adult. MIM‐1/39 was present in epithelial cells of the intervillous areas in the small intestine at 17 and 18 days of gestation; afterwards its expression was detected only in crypt cells from birth to adulthood. Transition from the mouth of the crypts to intestinal villi was abrupt. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…And the presence of these intestinal functional markers in HIEC indicated that these cells have some potential for functional differentiation. As a crypt cell marker, the detection of the MIM-1/39 antigen provided strong evidence that serially passaged HIEC still retained their epithelial character, a feature that was absent in Caco-2 and HIM cells (21,23). This may also indicate that HIEC had the characteristics of crypt cells (31).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…And the presence of these intestinal functional markers in HIEC indicated that these cells have some potential for functional differentiation. As a crypt cell marker, the detection of the MIM-1/39 antigen provided strong evidence that serially passaged HIEC still retained their epithelial character, a feature that was absent in Caco-2 and HIM cells (21,23). This may also indicate that HIEC had the characteristics of crypt cells (31).…”
Section: Discussionmentioning
confidence: 82%
“…Production of a rabbit-specific anti-mouse intestinal mucosa (MIM) -1/39 antibody has been described elsewhere (21)(22)(23).…”
Section: Primary Antibodiesmentioning
confidence: 99%
“…Indeed, the expression of intestinal epithelial-specific keratins [37], of components specific to cell junctions [38], cell cycle-related proteins [9,10,39], as well as typical intestinal cell markers of undifferentiated lower crypt cells [37,39,40] indicate that these cells behave as cells representative of the bottom of the human crypt [41]. Their epithelial cryptal origin was also confirmed by their ability to express the 350-kD crypt cell-specific marker MIM-1/39 [42]. Interestingly, we show herein that although EGF induced a rapid activation of ERK1/2 similarly to serum and LPA, this action was not sufficient for S phase entry as visualized by the absence of pRb hyperphosphorylation, cyclin A protein expression and E2F4 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…from MIM-1/130 hybridoma cells (125 µg protein/100 µl; group 3) or 100 µl anti-laminin antibodies in saline (106 µg protein/100 µl; group 4) twice daily for 3 days. Anti-laminin (clone LAM-1), a rat anti-mouse monoclonal antibody (ICN ImmunoBiological, Costa Mesa, Calif.) was of the same subclass as Mab-1/130 (Beaulieu et al 1992). This antibody recognizes laminin in a broad array of human and mouse basement membranes in cryostat sections.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…In this regard, the presence of an extracellular matrix molecule, the antigen MIM-1/130, expressed exclusively in the gastrointestinal tract and gallbladder (Beaulieu et al 1992) had raised much interest. At the fine structural level, this new component has been localized in the interstitial matrix around collagen fibrils surrounding fibroblasts of the pericryptal sheath and is absent from the basement membrane (Calvert et al 1994).…”
Section: Introductionmentioning
confidence: 99%